2017
DOI: 10.1007/s10964-016-0627-7
|View full text |Cite
|
Sign up to set email alerts
|

On the Development of Harmony, Turbulence, and Independence in Parent–Adolescent Relationships: A Five-Wave Longitudinal Study

Abstract: The separation-individuation, evolutionary, maturational, and expectancy violation-realignment perspectives propose that the relationship between parents and adolescents deteriorate as adolescents become independent. This study examines the extent to which the development of adolescents’ perceived relationship with their parents is consistent with the four perspectives. A latent transition analysis was performed in a two-cohort five-wave longitudinal study design covering ages 12–16 (n = 919, 49.2% female) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 44 publications
4
75
0
Order By: Relevance
“…In one study, only 14% of young adolescents (around age 12) reported turbulent relationships with parents characterized by low support and high conflict. Although this number increased to 29% in middle adolescence (around age 16) and decreased again to 10% in late adolescence (around age 20), most teenagers had the same type of relationship with their parents throughout adolescence . Thus, parent–adolescent dyads differ substantially and many do not experience increased conflict and decreased closeness.…”
Section: Change and Continuity In Relationshipsmentioning
confidence: 99%
“…In one study, only 14% of young adolescents (around age 12) reported turbulent relationships with parents characterized by low support and high conflict. Although this number increased to 29% in middle adolescence (around age 16) and decreased again to 10% in late adolescence (around age 20), most teenagers had the same type of relationship with their parents throughout adolescence . Thus, parent–adolescent dyads differ substantially and many do not experience increased conflict and decreased closeness.…”
Section: Change and Continuity In Relationshipsmentioning
confidence: 99%
“…Some forms of conflict can constitute physical (e.g., hitting with an open hand, fist, or other hard object) or psychological (e.g., threatening removal from home, insulting) maltreatment, which contribute to increased risk for internalizing and externalizing problems (Cohen, Menon, Shorey, Le, & Temple, ; Hagan, Roubinov, Mistler, & Luecken, ). Child maltreatment during childhood tends to continue through adolescence and emerging adulthood (Mercer et al., ), whereas more normative conflict tends to decrease over time alongside more independence during emerging adulthood (Hadiwijaya, Klimstra, Vermunt, Branje, & Meeus, ). Less research has examined the effect of continued adult child maltreatment by parents during emerging adulthood.…”
Section: Parental Psychopathologymentioning
confidence: 99%
“…Temple, 2017;Hagan, Roubinov, Mistler, & Luecken, 2014). Child maltreatment during childhood tends to continue through adolescence and emerging adulthood (Mercer et al, 2017), whereas more normative conflict tends to decrease over time alongside more independence during emerging adulthood (Hadiwijaya, Klimstra, Vermunt, Branje, & Meeus, 2017). Less research has examined the effect of continued adult child maltreatment by parents during emerging adulthood.…”
Section: Parental Psychopathologymentioning
confidence: 99%
“…Also, the association was strong among the adolescents aged 12-15. According to Hadiwijaya et al, as adolescents get older, hormonal changes act as the main force driving them to separate themselves from their parents to become autonomous and independent individuals [24]. It can be assumed that the importance of maternal accompaniment fades as the adolescents mature and perceive mental independence from their mothers.…”
Section: Discussionmentioning
confidence: 99%